2003
DOI: 10.1007/s00442-003-1210-y
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of leopard frogs to a pesticide mixture affects life history characteristics of the lungworm Rhabdias ranae

Abstract: We tested the hypothesis that exposure of leopard frogs ( Rana pipiens) to agricultural pesticides can affect the infection dynamics of a common parasite of ranid frogs, the lungworm Rhabdias ranae. After a 21-day exposure to sublethal concentrations of a pesticide mixture composed of atrazine, metribuzin, aldicarb, endosulfan, lindane and dieldrin, or to control solutions (water, dimethyl sulfoxide), parasite-free juvenile frogs were challenged with 30 infective larvae of R. ranae. Approximately 75% of the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(67 citation statements)
references
References 46 publications
2
62
1
2
Order By: Relevance
“…These pesticides also decreased eosinophils and increased encysted cercariae (Telorchis, Ribeiroia) in exposed amphibians (Kiesecker, 2002). Increased infections with parasites in pesticide-exposed amphibians have also been noted for R. ranae (Christin et al, 2003b;Gendron et al, 2003), Ribeiroia (Kiesecker, 2002) and trematode spp. (Rohr et al, 2008c), and Echinostoma trivolvis (Budischak et al, 2008;Rohr et al, 2008b).…”
Section: Environmental Pollutants and Pathogensmentioning
confidence: 87%
See 1 more Smart Citation
“…These pesticides also decreased eosinophils and increased encysted cercariae (Telorchis, Ribeiroia) in exposed amphibians (Kiesecker, 2002). Increased infections with parasites in pesticide-exposed amphibians have also been noted for R. ranae (Christin et al, 2003b;Gendron et al, 2003), Ribeiroia (Kiesecker, 2002) and trematode spp. (Rohr et al, 2008c), and Echinostoma trivolvis (Budischak et al, 2008;Rohr et al, 2008b).…”
Section: Environmental Pollutants and Pathogensmentioning
confidence: 87%
“…Exposure to atrazine and sodium nitrate decreased peripheral leukocyte levels, and increased infections with Ambystoma tigrinum virus (ATV) in Ambystoma tigrinum nebulosum (Forson and Storfer, 2006a;Forson and Storfer, 2006b). Gendron and others (Gendron et al, 2003) showed that 21days exposure to atrazine, metribuzin, aldicarb, endosulfan, lindane and dieldrin accelerated the migration of parasites into the lungs and increased the number of parasites in the lungs when pesticideexposed R. pipiens were subsequently challenged with the parasite R. ranae. After 7 weeks of development in water with no malathion, tadpoles previously exposed as embryos for only 96h to 60 and 600gl -1 malathion suffered from an increased number of E. trivolvis cysts when compared with controls (Budischak et al, 2008).…”
Section: Environmental Pollutants and Pathogensmentioning
confidence: 99%
“…Although they identified changes in the cellularity and phagocytic activity of X. laevis and in the lymphocyte proliferation of R. pipiens, suggesting increased susceptibility to infections, it was not possible to determine the relative contributions of the component pesticides or the interactions between them. Similarly, Gendron et al (2003) identified increased migration of lungworm in Rana pipiens exposed to a mixture of atrazine, metribuzin, aldicarb, endosulfan, lindane and dieldrin. Hayes et al (2006) determined the toxicity of individual pesticides at 0.1 ppb (alachlor, atrazine, cyfluthrin, l-cyhalothrin, S metalochlor, metalaxyl, nicosulfuron, propiconazole and tebupirimphos), a mix of all nine pesticides each at 0.1ppb, and that of a combination of atrazine and S-metalochlor at 0.1ppb and 10 ppb to leopard frogs (Rana pipiens) by assessing effects on larval growth and development, sex differentiation and immune function.…”
Section: Amphibiansmentioning
confidence: 90%
“…Given their lack of study, global distribution, and varied hosts, lungworms appear to be an ideal place to search for life cycle variation. Furthermore, the increasing popularity of lungworms as ideal host-parasite models to test evolutionary principles and ecological interactions (e.g., Goater, 1992Goater, , 1994Goater and Ward, 1992;Christin et al, 2003;Gendron et al, 2003;Dare andForbes, 2008a, 2008b) warrants a greater understanding of the worms' life histories. Our goal is to elucidate and compare the life cycles and life history characteristics of several Rhabdias spp.…”
mentioning
confidence: 99%